Literatur Review: Hubungan Model Hewan Coba (Faktor Jenis Kelamin dan Hormon) pada Sensitivitas Induksi Streptozotocin sebagai Agen Diabetogenik - Egi Claudia Pratiwi; Elsa Trinovita; Agnes Immanuela Toemon (Jurnal Surya Medika (JSM), 2022)
Diabetes mellitus (DM) is a metabolic disease that global concern and characterized by hyperglycemia. Tests for antidiabetic agents, either discovering new drugs or antidiabetic components, have been developed using experimental animals induced with the diabetogenic agent streptozotocin. The side effects of streptozotocin were reported lower than alloxan. The sensitivity of streptozotocin induction can be relied on by several factors such as sex and hormones—the difference in results in several studies regarding the relationship between streptozotocin induction sensitivity with gender. The research method is a literature review using a systematic approach. Articles are collected through search engines like NCBI, Google Scholar, and ResearchGate by entering keywords. Based on the results of data synthesis on the relationship between streptozotocin induction sensitivity and the sex of the experimental animal, it was found that fifteen articles were related and three articles were not. Sex has a relationship with streptozotocin induction's sensitivity through the hormones estrogen, progesterone, and testosterone.